The Lossen rearrangement from free hydroxamic acids. Issue 22 (15th May 2019) - Thomas, Mikaël; Alsarraf, Jérôme; Araji, Nahla; Tranoy-Opalinski, Isabelle; Renoux, Brigitte; Papot, Sébastien
Abstract : During more than a century, the Lossen rearrangement was supposed to occur exclusively in the presence of stochiometric amount of activating reagents. Very recently, it was demonstrated that the Lossen rearrangement can take place directly from free hydroxamic acids offering a renewal of interest for this reaction. Abstract : The Lossen rearrangement, that allows the conversion of hydroxamic acids into isocyanates, was discovered almost 150 years ago. For more than a century, this transformation was supposed to occur exclusively in the presence of stoichiometric amounts of activating reagents devoted to promoting the dehydration of primary hydroxamic acids. Very recently, it was demonstrated that the Lossen rearrangement can take place directly from free hydroxamic acids offering a renewal of interest for such a reaction. This short review summarizes advances in this field by describing successively the metal-assisted, the self-propagative and the promoted self-propagative Lossen rearrangement with a special emphasis on their mechanisms.